A shape control strategy for wire arc additive manufacturing of thin-walled aluminium structures with sharp corners. (April 2021) - Ding, Donghong; Zhao, Runzhuo; Lu, Qinghua; Pan, Zengxi; Li, Huijun; Wang, Kai; He, Kuanfang
Highlights: Self-overlapping in WAAM of thin-walled structures with sharp corners is revealed. A corner cross-section model for WAAM is established. Travel/welding speeds at corners are optimized by using the developed model. An improved deposition quality at corners can be achieved through using the proposed shape control strategy. Abstract: Wire Arc Additive Manufacturing (WAAM) of large thin-walled aluminium structures in the aerospace field has significant advantages over traditional subtractive approaches. The technique is based on arc welding and wire filler material, and the thin-walled structures are built up layer-by-layer. However, for the parts with sharp corners, the shape control poses a challenge due to the occurring of an inevitable self-overlapping of the deposition at corners. Since aluminium alloys are sensitive to heat, the undesired materials stacked at corners with excessive heat input reducing not only the shape accuracy of the deposited structures, but the stability of the deposition process also. In this paper, a shape control strategy was proposed to reduce shape errors through local optimization of deposition parameters at corners. A corner cross-section model correlating the relationship between the process parameter and bead profile in the self-overlapping area was firstly established. Accordingly, the parameter of the welding speeds at the corner areas were locally optimized with the proposed bead model. The performance of the present corner cross-section model was then investigated in terms of corners with the angle degree varied from 15° to 60°. Finally, the proposed shape control strategy was implemented through experiments on a thin-walled aluminium structure with varied sharp corners. It can be found that the accumulative height errors varied with the change of the angle degree of the corners. At the corner with the angle of 60°, the height error reduced from 3.56 mm to 1.75 mm corresponding to the average building height of 55.2mm. More than 50 % in error reduction was achieved indicating the considerable improvement of the proposed control strategy. This is critical in process planning to achieve better shape accuracy and material efficiency in the WAAM of thin-walled aluminium structures with sharp corners.